Community gastroenterologists can learn diminutive colon polyp histology characterization with narrow band imaging by a computer‐based teaching module. Issue 3 (8th December 2014) - Sinh, Preetika; Gupta, Neil; Rao, Deepthi S.; Wani, Sachin; Sharma, Prateek; Bansal, Ajay; Allen, John; Ketover, Scott R.; Rastogi, Amit
<x xml:space="preserve">Abstract</x> Background and Aim The aim of the present study was to evaluate the impact of a computer‐based teaching module on the performance of community gastroenterologists for characterization of diminutive polyps (≤5 mm) using narrow band imaging video clips. Methods Eighty videos were distributed in pre‐ and post‐test DVD along with a 20‐min audiovisual teaching presentation detailing endoscopic features differentiating adenomas from hyperplastic polyps using narrow band imaging. Each participant first reviewed pretest video clips and entered their responses for polyp histology and their confidence in diagnosis: high: ≥90% or low: <90%. Following this, they reviewed the teaching module and assessed the post‐test videos. Performance characteristics were calculated for pre‐ and post‐test videos by comparing predicted histology with actual histology. Fisher's exact test was used for analysis and the kappa statistic was calculated for interobserver agreement. Results Fifteen gastroenterologists in community practice completed the study. Sensitivity, specificity, accuracy and negative predictive value in characterization of polyp histology improved significantly post‐test compared to pretest. In post‐test, accuracy was 92% for high‐confidence diagnoses and the proportion of these increased with training from 46% (pretest) to 64% (post‐test); P < 0.001. Interobserver agreement for diagnosis improved from fair (kappa = 0.23) in pretest to moderate (kappa = 0.56) in post‐test. Conclusions A teaching module using video clips can be used to teach community gastroenterologists polyp histology characterization by narrow band imaging. Whether this translates into real‐time high accuracy in polyp detection needs to be further evaluated.